MK-6482 as a potential treatment for von Hippel-Lindau disease-associated clear cell renal cell carcinoma. (4th May 2021) - Hasanov, Elshad; Jonasch, Eric
ABSTRACT: Introduction: Von Hippel-Lindau (VHL) disease is an inherited autosomal dominant syndrome caused by a germline mutation and/or deletion of the VHL gene. Inappropriate hypoxia-inducible factor (HIF)-mediated transcription of proangiogenic and metabolic genes leads to the development of tumors and cysts in multiple organs. Surgery is a standard treatment for localized tumors with a risk of metastasis or organ dysfunction. Repeated surgeries cause substantial morbidity and have a major impact on quality of life. There is an urgent need to develop effective and safe systemic treatments for VHL disease manifestations. The small-molecule HIF 2 alpha inhibitor MK-6482 (belzutifan) has demonstrated significant efficacy in VHL disease related renal cell carcinomas, hemangioblastomas, and pancreatic neuroendocrine tumors while demonstrating an acceptable safety profile. Areas covered: This paper reviews the development of the HIF-2 alpha inhibitor, MK-6482, and discusses preliminary results of ongoing phase I/II studies in renal cell carcinoma (RCC) and VHL disease. An examination of ongoing clinical development of MK-6482 and perspectives on potential future developments and challenges are offered. Expert opinion: Because of its favorable safety profile, its clear efficacy in VHL disease, promising findings in sporadic, advanced RCC, and convenient oral formulation, MK-6482 is expected to become a leading treatment for VHL disease. Among other currently available oral agents, we believe that MK-6482 will be a preferred treatment for VHL-associated RCC.